P–618 D-Chiro-Inositol and mouse ovary: A new strange case of Dr Jekyll and Mr Hyde?. (6th August 2021) - Bevilacqua, A; Monastra, G; Tatone, C
Abstract: Study question: Low doses of D-Chiro-Inositol are beneficial in the treatment of a PCOS mouse model. However, high doses are detrimental for ovarian histology/function. Is D-Chiro-Inositol toxic for the mammalian ovary? Summary answer: Five mg/day D-Chiro-Inositol for 21 days produced PCOS-like histological/hormonal features. Ten/20 mg/day for 21 days induced ovarian/hormonal states resembling those typical of aged mice. What is known already: Administration of Myo-Inositol and D-Chiro-Inositol combined according to their plasma molar ratio of 40:1 has beneficial effects in the management of human PCOS. We confirmed the efficacy of this formulation, containing 0.2 mg/day D-Chiro-Inositol, in a mouse model of PCOS. However, formulations containing higher amounts of DCIns had negative effects on ovarian histology and mouse fertility. We investigated possible ovarian toxicity of D-Chiro-Inositol, studying its effects after administration to 30-day-old female mice for 21 days. Young adult mice reproduced the condition of young women possibly facing reproductive/metabolic problems, such as PCOS. Study design, size, duration: The effects of various doses of D-Chiro-Inositol were analysed on mouse ovarian histology, serum testosterone levels and expression of the ovarian enzyme aromatase. The 21-day period follows normal protocols of pharmacologic PCOS induction in the mouse and spans five ovulatory cycles. Doses employed, 5, 10, 20 mg/day, correspond to doses of 1200, 2400, 4800 mg/day in humans. The first dose is in the range of 1000–1500 mg/day currently prescribed to PCOS patients in clinical practice. Participants/materials, setting, methods: Five mice/treatment were provided with water administering various doses of D-Chiro-Inositol or 0, 5 mg/day letrozole as PCOS-positive controls, for 21 days. At the end of the period, ovulatory cycles were analysed by observations of vaginal cells after vaginal smears; ovarian histology was evaluated by sectioning, hematoxylin-eosin staining and light-transmission microscopy; serum testosterone levels were measured by ELISA; and expression of the ovarian enzyme aromatase was assayed by Western Blots. Main results and the role of chance: The estrus cycle progressed normally in negative control mice, but was arrested at day 8–10 in the majority of mice under all pharmacologic treatments. Uteri of negative control mice displayed the typical aspect of mature and cycling animals. Uteri of all other mice had an immature/metestrus-diestrus-like aspect, typical of non-cycling animals. Ovaries of negative control mice showed a normal presence of primary, secondary and tertiary follicles containing a growing oocyte, and of corpora lutea. Ovaries from mice treated with 5 mg/day D-Chiro-Inositol or 0, 5 mg/day letrozole had apparently normal primary and secondary follicles but also cystic tertiary follicles resembling those found in human PCOS. Ovaries from mice treated with 10 or 20 mg/day D-Chiro-Inositol had scarce primary and secondary follicles, a very limited number of tertiary follicles and no cystic follicles, but large follicles/areas with diffused cell proliferation. The typical ovarian structure was lost, especially in the highest dosage. Treatments with 5 mg/day D-Chiro-Inositol and 0, 5 mg/day letrozole increased serum testosterone levels above those of negative control mice, but the former reduced, while the latter increased aromatase levels relative to negative controls. Other treatments had no apparent effects on either testosterone or aromatase levels. Our experimental paradigm makes the role of chance highly improbable. Limitations, reasons for caution: The strength of our study relies on the use of an animal model representative of general human tissue organisation and physiological pathways. One weakness consists in the lack of data on serum estrogen levels, due to the paucity of blood provided by a single mouse and the ELISA sensitivity. Wider implications of the findings: Under all experimental conditions, D-Chiro-Inositol negatively affected ovarian histology and function. Notwithstanding physiological/biochemical differences between mice and humans, caution is therefore recommended when administering D-Chiro-Inositol to PCOS patients at doses corresponding to those we employed in the mouse and/or for long periods, since it may result ineffective or even toxic. Trial registration number: Not applicable